Pengaruh Audit Tenure, Pertumbuhan Perusahaan,Opinion Shopping Dan Opini Audit Tahun Sebelumnya Terhadap Penerimaan Opini Audit Going Concern(Studi Pada Perusahaaan Property And Real Estate Dan Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2014) - Said, Zuknan; , Fauzan, SE, Ak, M.Si (2016)
Going concern auditing opinion could become one thing to be considered by the financial repport users to make decisions before making investment. Going concern auditing opinion accepted by a company indicates the auditor's scepticism occurs about the life sustainability of the company. The purpose of the study is to determine the impact of audit tenure, growth'scompany, opinion shopping and prior year's opinionon receiving a going concern audit opinion. This research was conducted at the property and real estate and consumption industry companies listed in Indonesia Stock Exchange 2010-2014. The samples are selected by purposive sampling method. Amount of this sample research is 33 companies with a purposive sampling method. Data analysis techniques used in this research is logistic regression analysis. Based on the result, prove that the prior year's opinion variables significantly positive on receiving a going concern audit opinion. As for the variable audit tenure, growth of the company and opinion shopping where not significantly impact on receiving a going concern audit opinion.